Mindfulness-Based Cognitive Therapy and Self-Discrepancy in Recovered Depressed Patients with a History of Depression and Suicidality - Crane, C; Barnhofer, T; Duggan, D; Hepburn, S; Fennell, M; Williams, J (2008)
Long-term vulnerability to depression is related to the presence of perceived discrepancies between the actual self and ideal self-guides. This study examined the immediate effects of an 8-week course of Mindfulness-Based Cognitive Therapy (MBCT) on self-discrepancies in individuals currently in recovery, with a history of affective disorder that included suicidal ideation and behaviour. Results indicated significant time × group interactions for both ideal self similarity and ideal self likelihood ratings, primarily accounted for by increases in self-discrepancy from pre-test to post-test in the waiting list group which were not seen in those receiving MBCT. Changes in self-discrepancy were not associated with changes in residual depressive symptoms, but in the MBCT group there was a significant association between increases in ideal self similarity and the adoption of more adaptive ideal self-guides post treatment. MBCT may protect against increases in self-discrepancy in people vulnerable to relapse to depression and may also facilitate a shift in the goals of self-regulation. © 2008 Springer Science+Business Media, LLC.